Biting midges (Ceratopogonidae) as vectors of avian trypanosomes - Svobodová, Milena; Dolnik, Olga V; Čepička, Ivan; Rádrová, Jana (Parasites & vectors, 2017)
BACKGROUND: Although avian trypanosomes are widespread parasites, the knowledge of their vectors is still incomplete. Despite biting midges (Diptera: Ceratopogonidae) are considered as potential vectors of avian trypanosomes, their role in transmission has not been satisfactorily elucidated. Our aim was to clarify the potential of biting midges to sustain the development of avian trypanosomes by testing their susceptibility to different strains of avian trypanosomes experimentally. Moreover, we screened biting midges for natural infections in the wild. RESULTS: Laboratory-bred biting midges Culicoides nubeculosus were highly susceptible to trypanosomes from the Trypanosoma bennetti and T. avium clades. Infection rates reached 100%, heavy infections developed in 55-87% of blood-fed females. Parasite stages from the insect gut were infective for birds. Moreover, midges could be infected after feeding on a trypanosome-positive bird. Avian trypanosomes can thus complete their cycle in birds and biting midges. Furthermore, we succeeded to find infected blood meal-free biting midges in the wild. CONCLUSIONS: Biting midges are probable vectors of avian trypanosomes belonging to T. bennetti group. Midges are highly susceptible to artificial infections, can be infected after feeding on birds, and T. bennetti-infected biting midges (Culicoides spp.) have been found in nature. Moreover, midges can be used as model hosts producing metacyclic avian trypanosome stages infective for avian hosts.
Keywords: Trypanosomiasis; polymerázová řetězová reakce; Host specificity; trypanozomiáza; Avian parasite; Gastrointestinal Tract; Life-cycle; Canaries; hmyz - vektory; kanáři; nemoci ptáků; Culicoides nubeculosus; hostitelská specificita; ptáci; Birds; Animals; Trypanosoma avium; Microscopy, Electron, Scanning; zvířata; Bird Diseases; Ceratopogonidae; Trypanosoma bennetti; gastrointestinální trakt; Insect Vectors; Transmission; Polymerase Chain Reaction; Trypanosoma culicavium; mikroskopie elektronová rastrovací; Host Specificity; Trypanosoma